Ethnic variation, epidemiological factors and quality of life impairment associated with dyspepsia in urban Malaysia - Mahadeva, S.; Yadav, H.; Rampal, S.; Everett, S.M.; Goh, Khean Lee (Blackwell Publishing, 2010)
P>Background The role of ethnicity in the development of dyspepsia remains uncertain. Aims To examine the epidemiology of dyspepsia in a multi-ethnic Asian population and its impact on health-related quality of life (HRQOL). Methods A cross-sectional survey was conducted in a representative urban population in Kuala Lumpur, Malaysia. Results A total of 2039 adults (mean +/- s.d. age: 40.5 +/- 11.8 years, males 44.2%, ethnicity: Malays 45.3%, Chinese 38.0% and Indians 13.1%, tertiary education level 62%, professional employment 47.7% and median monthly income USD 850.00) were interviewed. Dyspepsia was prevalent in 496 (24.3%) adults. Independent predictors for dyspepsia, explored by logistic regression, were identified as: Malay (OR 2.17, 95% CI = 1.57-2.99) and Indian (OR 1.59, 95% CI = 1.03-2.45) ethnicity, heavy chilli intake (OR 2.35, 95% CI = 1.15-4.80), use of regular analgesia (OR 3.51, 95% CI = 2.54-4.87) and chronic illness (OR 1.67, 95% CI = 1.22-2.28). HRQOL was assessed with the EQ-5D and significantly lower scores were noted in dyspeptics compared with healthy controls (0.85 +/- 0.17 vs. 0.95 +/- 0.12, P < 0.0001). Conclusion Ethnicity, in addition to recognized epidemiological factors, is a risk factor for dyspepsia in an urban multi-racial Asian population.